PENGARUH PEMBERIAN INSENTIF DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN MONA PLAZA HOTEL PEKANBARU - Nani Pariani; Seno Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Important problem faced by the leadership at the hotel is how to maintain satisfaction so that it can support the successful achievement of goals . Strive to retain quality employees to work for a long time at the hotel is one of the hotel's goals. This research was conducted at Mona Plaza Hotel Pekanbaru . The purpose of this study was to determine the effect of incentives and work environment on employee job satisfaction at Mona Plaza Hotel Pekanbaru. Giving Incentives and Work Environment as independent variables (X1, X2) while Job Satisfaction as the dependent variable (Y). The problem in this study is the occurrence of fluctuating employee turnover and employee absenteeism. It can be seen from the company attendance. The sample of this study was taken as many as 31 respondents and the technique used was census. The data obtained from the results of the questionnaire were then processed and then tested statistically through the SPSS program. From the results of the tests conducted, it shows that the provision of incentives and the work environment has a positive and significant effect on employee job satisfaction at Mona Plaza Hotel Pekanbaru. Keywords: Giving Incentives, Work Environment, and Employee Job Satisfaction.